2011
DOI: 10.1097/ncc.0b013e3181f9a040
|View full text |Cite
|
Sign up to set email alerts
|

Coping, Quality of Life, Depression, and Hopelessness in Cancer Patients in a Curative and Palliative, End-of-Life Care Setting

Abstract: The observed relations between coping strategies, QOL, depression, and hopelessness give room to cognitive-behavioral nursing interventions. Specific attention is needed for differences in coping strategies between curative and palliative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 44 publications
(50 reference statements)
7
61
1
7
Order By: Relevance
“…These findings are consistent with previous research studies, demonstrating that cognitive coping mediates and moderates associations between various stressors and psychosomatic adjustment (20,41), but in contrast to other findings in another contexts (23,42,43). We find out that positive reappraisal negatively predicts the variance of resiliency.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These findings are consistent with previous research studies, demonstrating that cognitive coping mediates and moderates associations between various stressors and psychosomatic adjustment (20,41), but in contrast to other findings in another contexts (23,42,43). We find out that positive reappraisal negatively predicts the variance of resiliency.…”
Section: Discussionsupporting
confidence: 73%
“…In other words, a stronger illness identity, more symptoms, and a longer timeline perspective, were associated with poorer physical and psychological outcomes, while believing in cure/controllability were associated with better physical-psychological outcomes (16,17). some researchers found that people with psychical and mental diseases report more rumination and catastrophizing and less positive reappraisal than do healthy controlled subjects (18)(19)(20)(21); whereas, some researchers posed that rumination may facilitate coping process with chronic diseases (22). Other studies found that the habitual use of positive re-evaluation makes more resiliencies when faced with stressful events (23).…”
Section: Introductionmentioning
confidence: 99%
“…Among the PINE study cohort, the prevalence of suicidal ideation in the last two weeks, in the past twelve months and in life time was 3.5%, 4.8% and 9.4%, respectively. It is also reported that older age, female sex, lower education levels, lower income levels, living with fewer household members, lower overall health status, poorer quality of life, and worsened health changes over the last year were significantly correlated with suicidal ideation [28]. Additional analysis indicated that the level of perceived filial piety receipt from older adults' perceptive was associated with increased risk of suicidal ideation [29].…”
Section: Discussionmentioning
confidence: 93%
“…What is important, literature shows that the fighting spirit strategy, which was evaluated as the most important by the study of the lung cancer patient group, positively affects the assessment of one's quality of life [44]. Furthermore, if patients choose the helplessness-hopelessness or anxious preoccupation strategy, these tend to significantly lower their evaluation of the health-mediated quality of life [45,46].…”
Section: Discussionmentioning
confidence: 99%